Work‐related injury in NSW hospitalisation and workers' compensation datasets: a comparative analysis - Soufiane Boufous; Ann Williamson (Elsevier, 2003)
Abstract Objective:To undertake a comparative analysis of the New South Wales (NSW) Inpatient Statistics Collection (ISC) and Workers' Compensation Scheme Statistics (WCSS) for the 1999/2000 financial year in an attempt to evaluate their respective roles in the surveillance and monitoring of work‐related injuries in NSW. Methods:Work‐related injuries in ISC were identified mainly by using the ICD‐10 activity code and payment status and were compared with injury‐related claims reported in WCSS. Results:In 1990/2000, the majority of hospital separations for work‐related injury involved males (86.2%) who came into contact with various objects, including machinery and tools, representing the most common mechanisms of injury, and open wounds and fractures of the upper and lower limbs as the most common injury nature/location. Injuries reported in the WCSS were also dominated by males (70%), with muscular stress while handling objects as the most common mechanism of injury and sprain and strain of the lower back as the leading nature/location of injury. The proportion of workers aged 15-19 years in the WCSS (1.2%) was over five times lower than the proportion of the same age group recorded in the ISC. Conclusions and implications:The analysis indicates that the ISC and WCSS complement each other in characterising the burden of work‐related injuries in NSW. Linking compensation and outcomes data, including hospital admissions and emergency presentations, will provide a more comprehensive picture of the nature and the factors contributing to work‐related injuries. Such data will inform policy and program development aimed at reducing the burden of this type of injury in the community.